EFIKASI ISOLAT TRICHODERMA TERPILIH DENGAN BAHAN ORGANIK UNTUK MENGENDALIKAN PENYAKIT BUSUK PANGKAL BATANG PADA LADA DI LAPANGAN - Ginting, Cipta; Prasetyo, Joko; Nurhidayat, Aris; Maryono, Tri (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2017)
Efficacy of selected Trichoderma isolate and organic matter to control foot rot of black pepper in the field.Â The objective of this experiment was to determine the efficacy of selected Trichoderma isolatand organic matter to control the disease. Dual culture method was used to select a Trichoderma isolate. The experiment to evaluate the efficacy of selected isolate consisted of control (no application of T. harzianum or organic matter), T. harzianum and rice straw, and T. harzianum and coffee husk. As starter, T. harzianum was grown in broken rice. Two liters of organic matter was infested with suspension of 10 g starter in 100 ml steril water and incubated for 2 weeks. The mixture was applied around the base of black pepper stem. The results showed that all plants treated with T. harzianum and organic matter did not show disease symptom. Ten percent of the control plants showed symptoms. However, statistical analysis showed that the occurrence of the disease was not significantly different between treatments. Applications ofT. harzianum and rice straw increased the density of Trichoderma for 1 and 2 months after application. T. harzianum and coffee husk increased the density of the fungus 1 month after application.